(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This article presents the results of the research-creation project: Sentimental Drawing, multisensory experiences for the creation and contemplation of drawing, whose first result is Paths, an audiovisual piece in which sensory drawing is explored as a medium to recognize and trace the memory of the body. The work, a video performance, is constructed through contact with stretch marks on the skin, generating a process of graphic inscription that follows the traces time has left on the body. This action, which links tactile perception with drawing, caress with line, is conceived as a form of corporeal cartography in which the gesture of touching and tracing becomes a strategy for recognition and appropriation of one’s own image. The objective of this work is to explore the relationships between body, memory, and line, proposing an expanded view of drawing as a performative practice. To that end, the article examines theoretical references concerning the body as archive, and the ways in which the materiality of drawing can function as testimony and narrative. Finally, the work is analysed in the context of contemporary artistic practices that connect self-exploration with action and graphic gesture.